Pelatihan Keuangan dan Manajemen Usaha Agribisnis untuk Meningkatkan Kesejahteraan Petani di Desa Rejosari - Vina Oktariana; Subandi; Ayu Dian Pratiwi Permatahati; Ony Ilma Kumala Sari (Wisanggeni: Jurnal Pengabdian Masyarakat, 2022)
Farmers in Rejosari Village have problems in managing their finances before and after harvest, because what they do after getting the harvest is to pay debts as farmer capital. The aim of this service is to provide awareness to farmers that it is important to carry out financial management and business management to improve farmers' welfare. In this service, the methods used are lectures, questions and answers, exercises and discussions to improve the abilities of each farmer involved. To find out this, we use the SWOT method, namely Strengths, Weakness, Opportunities and Threats (SWOT) Analysis to improve the performance of each farmer. The findings that we have obtained are that so far farmers have never been given good and appropriate financial management training to create correct agribusiness management, so that up to now the level of farmer welfare has been measured by how much harvest they get. In fact, one indicator of increasing farmers' prosperity is how they receive financial training. The financial and business management training carried out has had a positive impact on farmers because it will make it easier for them to be more disciplined in financial management so that they can maximize the management of their agribusiness. Keywords: Kata kunci adalah finance, business management, farmers